2006
DOI: 10.1182/blood-2004-11-4403
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes form a vascular barrier and participate in vessel repair after brain injury

Abstract: Subpopulations of bone marrow-derived cells can be induced to assume a number of endothelial properties in vitro. However, their ability to form a functional vascular barrier has not been demonstrated. We report that human CD14 ؉ peripheral blood monocytes cultured under angiogenic conditions develop a number of phenotypic and functional properties similar to brain microvascular endothelial cells. These cells express the tight junction proteins zonula occludens 1 (ZO-1) and occludin and form a barrier with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…115 While this microparticle mediated response was associated with inhibition of pSrc (tyr416) signaling, a cause-effect relationship with endothelial barrier function was not demonstrated. In another study, 116 a different mechanism of monocytemediated protection was demonstrated. CD14C peripheral monocytes, cultured under angiogenic conditions, were shown to acquire phenotypic and functional properties similar to cerebral microvascular endothelial cells.…”
Section: Monocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…115 While this microparticle mediated response was associated with inhibition of pSrc (tyr416) signaling, a cause-effect relationship with endothelial barrier function was not demonstrated. In another study, 116 a different mechanism of monocytemediated protection was demonstrated. CD14C peripheral monocytes, cultured under angiogenic conditions, were shown to acquire phenotypic and functional properties similar to cerebral microvascular endothelial cells.…”
Section: Monocytesmentioning
confidence: 99%
“…It was proposed that CD14C blood monocytes may play an important role in repairing (sealing) the BBB after brain injury. 116 Platelets and endothelial barrier function Recently, much attention has been devoted to addressing the role of platelets in inflammation, and the evolving consensus is that platelets tend to amplify diffrent components of the inflammatory response, most notably the expression of endothelial cell adhesion molecules and the recruitment of leukocytes. 117,118 While there are some reports that describe the ability of platelets to diminish endothelial barrier function, 119 there is a larger body of evidence that supports an anti-permeability effect of platelets.…”
Section: Monocytesmentioning
confidence: 99%
“…In human populations, the use of Genome Wide Association Screening (GWAS) has identified a number of loci associated with CKD. 1,2 Further refinements to GWAS techniques using admixture-mapping linkage disequilibrium also allowed for the identification of a locus on chromosome 22q12 that predisposes individuals of African descent to nondiabetic glomerular injury, 3,4 and recent analyses strongly indicate that the affected gene is ApoL1. 5,6 Undoubtedly, other genes are involved in development of progressive kidney disease.…”
Section: Disclosuresmentioning
confidence: 99%
“…EPCs are now widely described to promote capillary repair and restoration by a number of mechanisms, including canalization of new capillary tracts, temporary (days to weeks) replacement of endothelial cells in areas of denuded capillary basement membrane, new capillary basement membrane synthesis, cytokine release that promotes endothelial cell proliferation, and adoption of pericyte functions. 4,5 But can the endogenous reparative functions of macrophages be harnessed for good in the kidney? It seems so.…”
mentioning
confidence: 99%
“…From a mechanistic point of view, the absence of an independent association between chemokines involved in monocyte/ macrophage trafficking (MCP-1 or IL-8) and incident symptomatic CHD or stroke is, a posteriori, not completely unexpected. Besides its role in the promotion of inflammatory atherosclerotic lesion growth, monocyte/macrophage recruitment into the ischemic brain or myocardium is also required to ensure adaptive collateral vessel growth, neovascularization, and tissue repair, 31,32 all of which might significantly limit disease severity and reduce the occurrence/incidence of sustained symptomatic disease. In addition, resident microglia greatly contributes to the response of the brain to injury, 33 possibly substituting for and substantially limiting the need for monocyte recruitment.…”
Section: Discussionmentioning
confidence: 99%